Postcolonial Exceptionality and the Portuguese Language: José Eduardo Agualusa’s The Book of Chameleons - Schor, Patricia (FRAME, Journal of Literary Studies, 2026)
Language discourse attached to Portuguese national culture has been critical for the re-establishment of the imperial centre in the space of encounter between Portugal and its former colonies. The Angolan writer José Eduardo Agualusa has been problematising this centrality; both criticising and re-enacting the mythology of a benevolent colonial encounter à la Portuguese. This article analyses the representations of the Portuguese language in Agualusa’s novel The Book of Chameleons. It unravels the author’s negotiations with the postcolonial narrative of imperial exceptionality, concluding about the transgressive quality of Agualusa’s language imagination.